The Influence Of Financial Literacy, Ease Of Use Of E-Money, And Digital Lifestyle On Gen Z Consumptive Behavior - Putri Dwi Nurul Luthfi; Herry Achmad Buchory (UNIVED Press, 2026)
This study aims to examine the effect of financial literacy, perceived ease of use (PEOU) of e-money, and income on the consumptive behavior of Generation Z, with digital lifestyle as a mediating variable. The background of this study is the high consumptive tendency of LPK Prasetya Putri students, such as impulsive purchases due to discounts, trends, and social media, which has an impact on the difficulty of paying tuition fees. The method used was quantitative with a descriptive-verification approach, and data were obtained through a survey of 204 Gen Z students. The analysis was conducted using SEM PLS-4. The results show that digital lifestyle is in the very high category, consumptive behavior is high, and PEOU e-money and income are in the moderately high category, while financial literacy is moderate.Descriptively, the dominant indicator in consumptive behavior is impulse buying, and in digital lifestyle is daily digital activity. Verifiably, financial literacy and PEOU e-money have no direct influence on consumptive behavior, but have a significant effect through digital lifestyle (full mediation). In contrast, income has a direct and indirect influence on consumptive behavior (partial mediation). This study confirms that digital lifestyle has an important mediating role in shaping Generation Z consumptive behavior.